Targeted alpha-particle therapy in neuroendocrine neoplasms: A systematic review - Thuan Koh; Eva Bezak; David Chan; Gabrielle Cehic (World Journal of Nuclear Medicine)
Neuroendocrine neoplasms (NENs) are a very diverse group of tumors with a worldwide rise in incidence. Systemic therapy remains the mainstay treatment for unresectable and/or metastatic NENs. 177Lu-DOTATATE, a radiopharmaceutical which emits beta particles, has emerged as a promising therapy for metastatic gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs). However, limited treatment options are available particularly after the failure of 177Lu-DOTATATE therapy. This review aims to identify and summarize the available evidence for, and potential adverse events of, targeted alpha-particle therapy (TAT) in the treatment of metastatic NENs, specifically GEP-NENs. The MEDLINE, EMBASE, SCOPUS, and Cochrane Library databases were searched. Two articles which met the inclusion criteria were identified and included in the review. Putative radiopharmaceuticals that can be considered for metastatic NEN treatment include 225Actinium (225Ac)-DOTATATE and 213Bismuth (213Bi)-DOTATOC. There was evidence of partial response using both radiopharmaceutical agents without significant hematological, renal, or hepatotoxicity. Future studies should consider longer term, randomized controlled trials investigating the role of TAT, in particular, 225Ac-DOTATATE, in the treatment of metastatic NENs.